Stosunki handlowe pomiędzy Unią Europejską a wybranymi krajami azjatyckimi - Adamczyk, Marzena; Piasecka-Głuszak, Agnieszka (Trade Relations between the European Union and Selected Asian Countries, 2008)
Asian countries have become more important in the world economy. Asia as a whole is the European Union's second-largest regional trading partner (the first one is North America). This article's objective is to present trade relations between the European Union and selected Asian countries. It contains examples of trade agreements signed between the EU and North-East Asian and South-East Asian countries. It shows also the importance and contribution of these countries to the union trade. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 9-24